A single day of TGF-β1 exposure activates chondrogenic and hypertrophic differentiation pathways in bone marrow-derived stromal cells - Kathryn Futrega (Nature Portfolio, 2021)
Futrega et al. challenge the long established chondrogenic differentiation protocol used to induce bone marrow-derived stromal cell (BMSC) differentiation which presumes the need for more than 2 weeks of continuous TGF-β1 exposure. Using a micro-pellet model, they show that BMSC differentiation is triggered by a single day of TGF-β1 exposure.